THE ROLE OF MADRASAH PRINCIPAL LEADERSHIP IN TECHNOLOGY-BASED EDUCATIONAL INNOVATION - Taskya Nafsi Al Husna; Nur Hidayati (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This study aims to describe the role of the madrasah principal’s leadership in  encouraging technology-based educational innovation, as well as to describe the  strategies employed by the principal in utilizing technology to improve the quality  of education. The research adopts a qualitative approach, which involves  investigating phenomena in their natural settings and employs a descriptive  research design. The selection of informants was carried out using the snowball  sampling technique, beginning with initial informants and subsequently expanding  by seeking recommendations for additional informants relevant to the research  focus. Data collection techniques included observation, interviews, and  documentation. The data analysis procedures consisted of data reduction, data  presentation, and conclusion drawing al well as SWOT. The results of the study indicate that the madrasah principal plays a role as an  initiator of digital learning programs. This includes innovations implemented in the  madrasah, such as the use of platforms like Google Classroom, Madrasah e learning, the Madrasah SIM Dashboard, the use of videos in instructional methods,  and online evaluation. The principal’s role is not limited to structural leadership;  the principal also serves as a role model in the use of technology, both in  management practices and academic supervision. This strategy not only  demonstrates the principal’s commitment to developing educational innovation but  also reflects systematic, participatory, and adaptive planning in response to the  dynamics of 21st-century education. This study contributes to the development of  research in educational management and leadership, particularly within the  context of madrasah.